APPROACHES AND ACTIVITIES TO DEVELOP INTERCULTURAL COMPETENCE (Web of Teachers: Inderscience Research, 2023)
The article describes the role of approaches and activities to develop intercultural competence in teaching and learning process. Approaches and activities generally integrate language and cognitive skills, connect to real-life problems, generate high learner interest, and involve some cooperative or group learning skills.